Pelatihan Pengembangan Media Pembelajaran 3D pada Guru Kelas di SDN Negeri 057761 Kwala Gebang - Rusli Rusli (Institut Teknologi dan Bisnis Semarang, 2023)
Elementary School (SD), as one of the early grades of Early Childhood Education, is a learning institution that participates in educating the nation's children through classroom learning. The purpose of community service in implementing 3D learning media about building space for Elementary Schools (SD) is to achieve elementary students' understanding of nets, properties, surface area, and volume of spatial objects. Service Learning is the approach or method used (SL). A service-learning method is a teaching approach that combines academic goals to raise awareness of directly solving problems. The implementation of a community service project involving the use of 3D learning media to teach elementary school students about building space yielded positive results. This can be seen when the process of applying the learning media results in nearly 80% of students participating in learning with enthusiasm. They were very enthusiastic about listening to the teacher's explanation after the teacher received training from the community service team. Due to the availability of learning media, students felt more interested in and understood the material presented much better.